The Photocatalytic and Biological Activity of Cuucumin Coated with Lanthanumdoped Copper Oxide Nanoparticles - Y. Prashanthi, (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: The study focuses on the synthesis and evaluation of curcumin-coated lanthanum-doped copper oxide (La-CuO) nanoparticles (NPs), aiming to combine the bioactivity of curcumin with the photocatalytic and antimicrobial properties of La-CuO. Materials and Methods: Curcumin-coated La-CuO NPs were characterized using transmission electron microscopy, scanning electron microscopy, Fourier-transform infrared and X-ray diffraction, providing insights into their morphology, size distribution, functional groups, crystalline structure, and phase composition. The study explored the photocatalytic effects of these NPs on thiodicarb pesticide residues in water, revealing that the NPs significantly reduced the pesticides’ half-life when exposed to sunlight. In addition, curcumin, a compound in turmeric, is noted for its anti-diabetic properties, including blood sugar control, oxidative stress reduction, and enhanced insulin sensitivity. Results and Discussion: Photocatalysis studies show increased efficiency and faster reactions, and the DT50 value, or half-life, is important in environmental chemistry. This study suggests new uses for curcumin-coated La-CuO NPs in environmental remediation and wastewater treatment. Curcumin-coated La-CuO NP’s antidiabetic effects were evaluated by inhibiting the α-glucosidase enzyme. Conclusion: According to this study, CuO NPs inhibit diabetes by 40.23%. La-CuO NPs coated with curcumin have been shown to have promising antidiabetic properties. According to research, turmeric’s polyphenol curcumin may have insulin-sensitizing properties that aid in blood sugar control. Curcumin has been shown to improve β-cell function, reduce insulin resistance, and prevent β-cell death, making it a promising treatment for diabetes.